Negative Impacts From the Shift to Online Learning During the COVID-19 Crisis: Evidence From a Statewide Community College System. (April 2022) - Bird, Kelli A.; Castleman, Benjamin L.; Lohner, Gabrielle
The COVID-19 pandemic led to an abrupt shift from in-person to virtual instruction in the spring of 2020. We use two complementary difference-in-differences frameworks: one that leverages within-instructor-by-course variation on whether students started their spring 2020 courses in person or online and another that incorporates student fixed effects. We estimate the impact of this shift on the academic performance of Virginia's community college students. With both approaches, we find modest negative impacts (3%–6%) on course completion. Our results suggest that faculty experience teaching a given course online does not mitigate the negative effects. In an exploratory analysis, we find minimal long-term impacts of the switch to online instruction.